Effects of Pharyngeal Electrical Stimulation on Swallow Timings, Clearance and Safety in Post-Stroke Dysphagia: Analysis from the Swallowing Treatment Using Electrical Pharyngeal Stimulation (STEPS) Trial - Everton, Lisa F. (Stroke Res Treat, 2021)
Swallowing impairment (dysphagia) post-stroke results in poorer outcomes. Pharyngeal electrical stimulation (PES) is a potential treatment for post-stroke dysphagia. In a post hoc analysis, we investigated PES using videofluoroscopy swallow studies (VFSS) from the STEPS trial incorporating multiple measures of safety (penetration aspiration scale-PAS), speed and duration (timing), and efficiency (clearance), as opposed to the original trial which only measured PAS scores. 81 randomised participants (PES (N = 43) versus sham (N = 38)) were analysed at baseline and 2 weeks. Participants swallowed up to 6 × 5 ml and 1 × 50 ml of thin liquid barium at 40% w/v, images at ≥25 fps. Based on PAS, the 5 ml mode bolus (most frequently occurring PAS from 6 × 5 ml) and the worst 50 ml bolus were chosen for further analysis. Eight timing measures were performed, including stage transition duration (STD) and pharyngeal transit time (PTT). Clearance measures comprised oral and pharyngeal residue and swallows to clear. Comparisons of change of scoring outcomes between PES and sham were done at 2 weeks. Wilcoxon Signed Ranks Test was also used to evaluate longitudinal changes from both groups' combined results at two weeks. Between-group analysis showed no statistically significant differences. Issues with suboptimal image quality and frame rate acquisition affected final numbers. At two weeks, both groups demonstrated a significant improvement in most safety scores (PAS) and STD, possibly due to spontaneous recovery or a combination of spontaneous recovery and swallowing treatment and usual care. A nonsignificant trend for improvement was seen in other timing measures, including PTT. This study, which conducted additional measurements of kinematic and residue analysis on the STEPS data did not detect “missed” improvements in swallowing function that the PAS is not designed to measure. However, more studies with greater numbers are required.